Perbedaan Fungsi Penggunaan Modalitas Nakerebanaranai, Beki dan Hazu dalam Komik Chibi Maruko Chan dan Detektif Conan - Fennie Fennie; Nalti Novianti (Lingua Cultura, 2010)
There are many grammatical category in Japanese language, one of them is grammatical category in predicate. For examples is modality. Modality has divided into many kinds, for examples is toui modality and gaigen modality. Between toui modality and gaigen modality, writer want to analyze about differences uses between nakereba naranai 「なければならない」, beki「べき」dan hazu「はず」. Article analyzes this topic because the writer want to understand about the differences using toui modality and gaigen modality. For analyze, the writer use Chibi Maruko Chan 9 and Detektif Conan jilid 7, 9, 37 and 38 that used Japanese language as an object. The used methods in this article is descriptive analytic. As a conclusion, these modality can substitute each others. This substitutin is based on the situations and context.